DM506 (3-Methyl-1,2,3,4,5,6-hexahydroazepino[4,5-b]indole fumarate), a Novel Derivative of Ibogamine, Inhibits α7 and α9α10 Nicotinic Acetylcholine Receptors by Different Allosteric Mechanisms - Tae, Han Shen (2023)
The main objective of this study was to determine the pharmacological activity and molecular mechanism of action of DM506 (3-methyl-1,2,3,4,5,6-hexahydroazepino[4,5-b]indole fumarate), a novel ibogamine derivative, at different nicotinic acetylcholine receptor (nAChR) subtypes. The functional results showed that DM506 neither activates nor potentiates but inhibits ACh-evoked currents at each rat nAChR subtype in a non-competitive manner. The receptor selectivity for DM506 inhibition follows the sequence: α9α10 (IC50 = 5.1 ± 0.3 μM) ≅ α7β2 (5.6 ± 0.2 μM) ∼ α7 (6.4 ± 0.5 μM) > α6/α3β2β3 (25 ± 1 μM) > α4β2 (62 ± 4 μM) ≅ α3β4 (70 ± 5 μM). No significance differences in DM506 potency were observed between rat and human α7 and α9α10 nAChRs. These results also indicated that the β2 subunit is not involved or is less relevant in the activity of DM506 at the α7β2 nAChR. DM506 inhibits the α7 and α9α10 nAChRs in a voltage-dependent and voltage-independent manner, respectively. Molecular docking and molecular dynamics studies showed that DM506 forms stable interactions with a putative site located in the α7 cytoplasmic domain and with two intersubunit sites in the extracellular-transmembrane junction of the α9α10 nAChR, one located in the α10(+)/α10(─) interface and another in the α10(+)/α9(─) interface. This study shows for the first time that DM506 inhibits both α9α10 and α7 nAChR subtypes by novel allosteric mechanisms likely involving modulation of the extracellular-transmembrane domain junction and cytoplasmic domain, respectively, but not by direct competitive antagonism or open channel block.